1991
DOI: 10.2307/2409490
|View full text |Cite
|
Sign up to set email alerts
|

Testing Inferences about Microevolutionary Processes by Means of Spatial Autocorrelation Analysis

Abstract: We generated numerous simulated gene-frequency surfaces subjected to 200 generations of isolation by distance with, in some cases, added migration or selection. From these surfaces we assembled six data sets comprising from 12 to 15 independent allele-frequency surfaces, to simulate biologically plausible population samples. The purpose of the study was to investigate whether spatial autocorrelation analysis will correctly infer the microevolutionary processes involved in each data set. The correspondence betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0
8

Year Published

1993
1993
2006
2006

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 6 publications
9
70
0
8
Order By: Relevance
“…A similar pattern of genetic structure was predicted from computer simulations of populations with restricted gene flow (e.g., Sokal and Jacquez 1991;Epperson and Li 1997;Sokal et al 1997;Epperson et al 1999) and has also been reported in empirical studies of plants (e.g., Smouse and Peakall 1999) and mammals (Peakall et al 2003). Similarly, the autocorrelation analysis of female fairy-wrens alone detected significant positive genetic correlation but only in the 40-and 80-m distance classes.…”
Section: Due To Their Propensity To Disperse Females Will Show No Spsupporting
confidence: 81%
“…A similar pattern of genetic structure was predicted from computer simulations of populations with restricted gene flow (e.g., Sokal and Jacquez 1991;Epperson and Li 1997;Sokal et al 1997;Epperson et al 1999) and has also been reported in empirical studies of plants (e.g., Smouse and Peakall 1999) and mammals (Peakall et al 2003). Similarly, the autocorrelation analysis of female fairy-wrens alone detected significant positive genetic correlation but only in the 40-and 80-m distance classes.…”
Section: Due To Their Propensity To Disperse Females Will Show No Spsupporting
confidence: 81%
“…To gain insight into the relationship between autocorrelation and heterozygosity, computer simulations of an isolation-by-distance process were carried out following Sokal & Wartenberg (1983) and Sokal & Jacquez (1991 It should be noted that in these simulations the same reproduction event involves all loci of a tree independent of their heterozygosities, so that similar patterns of genetic spatial structuring should be produced for all loci.…”
Section: Methodsmentioning
confidence: 99%
“…Further investigation of this topic is necessary, but there is a possibility that the increasing rate of evolution, associated with selection, may produce higher slopes in the correlogram. Another possibility, following the inferential procedures in spatial autocorrelation, is that multivariate (or multivariable) analysis can be useful to distinguish between different processes (Sokal and Jacquez, 1991). Other methods have been proposed to distinguish between Brownian motion and O-U processes, but their application in this study would be difficult, because of limitations in the data set.…”
Section: Discussionmentioning
confidence: 99%